Topoisomerase Assays. Issue 10 (4th October 2021) - Nitiss, John L.; Kiianitsa, Kostantin; Sun, Yilun; Nitiss, Karin C.; Maizels, Nancy
Abstract: Topoisomerases are enzymes that play essential roles in DNA replication, transcription, chromosome segregation, and recombination. All cells have two major forms of DNA topoisomerases: type I enzymes, which make single‐stranded cuts in DNA, and type II enzymes, which cut and decatenate double‐stranded DNA. DNA topoisomerases are important targets of approved and experimental anti‐cancer agents. Provided in this article are protocols to assess activities of topoisomerases and their inhibitors. Included are an assay for topoisomerase I activity based on relaxation of supercoiled DNA; an assay for topoisomerase II based on the decatenation of double‐stranded DNA; and approaches for enriching and quantifying DNA‐protein covalent complexes formed as obligatory intermediates in the reactions of type I and II topoisomerases with DNA; and assays for measuring DNA cleavage in vitro . Topoisomerases are not the only proteins that form covalent adducts with DNA in living cells, and the approaches described here are likely to find use in characterizing other protein‐DNA adducts and exploring their utility as targets for therapy. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Assay of topoisomerase I activity Basic Protocol 2 : Assay of topoisomerase II activity Basic Protocol 3 : In vivo determination of topoisomerase covalent complexes using the in vivo complex of enzyme (ICE) assay Support Protocol 1 : Preparation of mouse tissue for determination of topoisomerase covalent complexes using the ICE assay Support Protocol 2 : Using recombinant topoisomerase standard for absolute quantification of cellular TOP2CC Basic Protocol 4 : Quantification of topoisomerase‐DNA covalent complexes by RADAR/ELISA: The rapid approach to DNA adduct recovery (RADAR) combined with the enzyme‐linked immunosorbent assay (ELISA) Basic Protocol 5 : Analysis of protein‐DNA covalent complexes by RADAR/Western Support Protocol 3 : Adduct‐Seq to characterize adducted DNA Support Protocol 4 : Nuclear fractionation and RNase treatment to reduce sample complexity Basic Protocol 6 : Determination of DNA cleavage by purified topoisomerase I Basic Protocol 7 : Determination of inhibitor effects on DNA cleavage by topoisomerase II using a plasmid linearization assay Alternate Protocol : Gel electrophoresis determination of topoisomerase II cleavage